Hermite-Hadamard type inequalities by using Newton-Cotes quadrature formulas - Angshuman R. Goswami; Ferenc Hartung (Miskolc Mathematical Notes)
A convex function f:[a,b]→ℝ f (a+b2)≤1b−a∫ abf(t)dt≤f(a)+f(b)2. 1b−aIn(f)In(f)